Learning English and Spanish in Times Od Covid-19 in A Slavic-Speaking Country (Memorias Sifored - Encuentros Educación UAN, 2021)
The following report is a glimpse at certain strategies which are currently used during the juncture caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) COVID-19. Owing to the COVID-19 upbreak many schools, including universities, high school as well as language schools have to face many difficulties and seek for novel policies to keep their lessons coming. 4idiomas S.R.O is a language school based on the Czech Republic, a Slavic-speaking country which its population is prone to learn foreign languages on account of the worldwide use of English and Spanish in contrast to the comparatively lower number of Czech speakers. This contribution shall deepen into the plans that were implemented to face such a demanding challenge, such as skype, meet, whereby along with sharing documents, home works and other kind of assignments. The findings of this implementations suggest that despite the reluctance and rejection that many students showed during the first, they began accepting and even liking the online lessons, in that extent, that there are students who hitherto rather have online lessons than face-to-face ones.